Analisis Kerusakan Sea Water Cooling Pump pada Mesin Induk di Kapal MV. Sjw Mountain - George Jonhanes Baramata; Maxima Ari Saktiono; Sugeng Marsudi (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Sea water cooling pump is a vital component of the main engine cooling system, responsible for circulating seawater to absorb engine heat. Damage to Sea water cooling pump No. 2 on MV. Sjw Mountain reduced pump pressure from the normal range of 3.5–3.9 bar to 1.5–1.9 bar, causing the cooling system temperature to increase to 80°C and increasing the risk of engine overheating. This study aimed to identify the causes of pump failure, evaluate the level of failure risk, and determine appropriate corrective actions. The research employed the Fishbone diagram and Failure Mode and Effect Analysis (FMEA). Data were collected through observations, interviews with ship engineers, documentation, and questionnaires administered to the Chief Engineer, Second Engineer, Third Engineer , Fourth Engineer, and Oiler. The Fishbone analysis identified five contributing factors: man, method, machine, material, and environment. FMEA results showed that the method factor had the highest Risk Priority Number (RPN) of 210, followed by environment (175), machine (160), material (120), and man (100). The study concluded that inadequate inspection and maintenance practices were the primary causes of pump failure. Recommended improvements include strengthening the Planned Maintenance System (PMS), conducting regular inspections, replacing worn components, and improving crew supervision to maintain optimal cooling system performance.